SEMANTICS OF THE SPEECH VERBS SPEAK, TALK IN THE ENGLISH LANGUAGE - Ziyoyeva , Dilnoza Anvarovna (Innovative Development in Educational Activities, 2023)
Semantics the branch of linguistics and logic concerned with meaning. The two main areas are logical semantics, concerned with matters such as sense and reference and presupposition and implication, and lexical semantics, concerned with the analysis of word meanings and relations between them. Semantics is the study of the meaning of words and sentences. It uses the relations of linguistic forms to non-linguistic concepts and mental representations to explain how sentences are understood by native speakers. This article devoted to the classification of the speech verbs and semantic characteristics of the verbs speak, talk in the English language.